SCIENTIFIC EVALUATION OF SEASONAL DIETARY PRACTICES IN KERALA – KARKITAKA KANJI, MUKKUDI, PATTILA CURRY (AYUSHDHARA, 2021)
Following a seasonal dietary regimen is an age old practice amongst the mankind which enabled them to survive and adapt according to the environmental needs. But the urbanization took away most of such culturally bound time tested practices from the society which played a key role in maintaining good health and immunity. Karkitaka Chikitsa – (a systematically following dietary and therapeutic regimens during the month of Karkidam (June-July)- is one such practice which is still prevailing in the south Indian states especially in Kerala. The month of Karkidaka is in the transition phase from rainy season to autumn characterized with debilitated health and lack of employment due to climatic conditions. According to Ayurveda the strength of body is considerably compromised during the months of summer and rainy season. Poor digestive power (Agni bala) and aggravation of Vata dosha happens during the rainy season. Hence specific diet and therapeutic regimens that can mitigate or balance the Vata and thereby rejuvenate the health and immunity is followed. The dietary plans include Karkkidaka kanji (rice gruel processed with herbs), Mukkudi, Pattila curry (dish made with ten varieties of leaves) etc. This article is an attempt to scientifically analyze the special monsoon dietetics of Kerala.